(3d+1)(d+4)=0

Simple and best practice solution for (3d+1)(d+4)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3d+1)(d+4)=0 equation:


Simplifying
(3d + 1)(d + 4) = 0

Reorder the terms:
(1 + 3d)(d + 4) = 0

Reorder the terms:
(1 + 3d)(4 + d) = 0

Multiply (1 + 3d) * (4 + d)
(1(4 + d) + 3d * (4 + d)) = 0
((4 * 1 + d * 1) + 3d * (4 + d)) = 0
((4 + 1d) + 3d * (4 + d)) = 0
(4 + 1d + (4 * 3d + d * 3d)) = 0
(4 + 1d + (12d + 3d2)) = 0

Combine like terms: 1d + 12d = 13d
(4 + 13d + 3d2) = 0

Solving
4 + 13d + 3d2 = 0

Solving for variable 'd'.

Factor a trinomial.
(4 + d)(1 + 3d) = 0

Subproblem 1

Set the factor '(4 + d)' equal to zero and attempt to solve: Simplifying 4 + d = 0 Solving 4 + d = 0 Move all terms containing d to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + d = 0 + -4 Combine like terms: 4 + -4 = 0 0 + d = 0 + -4 d = 0 + -4 Combine like terms: 0 + -4 = -4 d = -4 Simplifying d = -4

Subproblem 2

Set the factor '(1 + 3d)' equal to zero and attempt to solve: Simplifying 1 + 3d = 0 Solving 1 + 3d = 0 Move all terms containing d to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 3d = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 3d = 0 + -1 3d = 0 + -1 Combine like terms: 0 + -1 = -1 3d = -1 Divide each side by '3'. d = -0.3333333333 Simplifying d = -0.3333333333

Solution

d = {-4, -0.3333333333}

See similar equations:

| 7z+1=8z-7 | | 7(x-3)=3x+2 | | 10x-x=x+4+7x | | 2y+(y+600)=5010 | | Y=-5/3x | | 2x-4x=4+8 | | 1/5x25 | | 8x+4y-2z= | | a^2+17+72= | | 12x+7=18x-23 | | 2x/3=x-15 | | 23=3p-1 | | x^2-6x+9*4x-x*4x-5=0 | | 20(x-5+2)=6 | | 2(y-1)-3=11 | | 2(w-1)/4=2-w | | 8(x+100)+3=837 | | 4xw*5w= | | 8x^2-56x+96=8(x-3)(x-4) | | -6x=42y | | 3g+5(g-2)= | | 64=n-8 | | 15p+16q+p-5q-4p= | | y-5x=-30 | | 6x^2-6xy= | | 3(2x-1)+2x=1-4(x-2) | | 6(1)-2y=6 | | 14a+15b+5c+4c-4b-2a= | | 3d+9e+10d+8e= | | 2x/3=x-5 | | 4/3×-1/2= | | 4/3×-1/2=0 |

Equations solver categories